PERBANDINGAN MODEL PEMBELAJARAN JIGSAW DAN TEACHING GAMES FOR UNDERSTANDING UNTUK MENINGKATKAN KETERAMPILAN SERVIS BACKSPIN BACKHAND SISWA KELAS XI DALAM PERMAINAN TENIS MEJA - Cipto Nazzario Putra; Wahyu Saputra; Asep Akbaruddin; Mochammad Fajar Permana; Gugun Gunawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aimed to investigate the effect of Jigsaw and Teaching Games for Understanding (TGFU) learning models on the backspin backhand serve skills of table tennis in class XI students of SMKN 1 Subang. This study was an experimental method with a pre-test post-test design. The population in this study were all students of class XI SMKN 1 Subang, the sample of this study were 40 people. The instrument used for data collection was the table tennis backspin backhand service skill test. The results showed that the Jigsaw learning model pre-test mean was 26.45 and the post-test mean was 15.45, with the lowest score being 21 and the highest being 32. While the TGFU type group obtained a pre-test mean score of 26.30 and a post-test mean of 15.75. With the lowest number 21 and the highest number 32. In the paired-test test in hypothesis one, the Jigsaw Type method shows a significant value of .000 and for hypothesis two the TGFU Type Method shows a significant value of .000. whereas the three hypothesis tests of the Jigsaw Type Method and the TGFU Type Method show the same results .567. then the difference is calculated, the Jigsaw Type Method is 0.55, while the TGFU Type Method is 0.53. so it can be concluded that the Jigsaw Type Method on the backspin backhand tennis table service at SMKN 1 Subang is better than the TGFU Type Method.